ISLAMIC RELIGIOSITY GUIDANCE APPROACHES ON MENTAL HEALTH DISORDER - Awang Saputra; Adi Fahrudin; Munaya Fauziah; Saiful Bahri; Muhammad Fachri (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
The productive age population in Indonesia in 2022 will reach 69%, with great potential for increasing economic growth. However, there is an increasing threat of mental disorders, which results in low productivity and hinders economic growth. Mental health disorders have psychologically weak conditions that need strengthening through religious guidance. Muslims believe that a religious guidance approach can help solve problems of mental health disorders. Unfortunately, they do not understand practical Islamic guidance as an effort to prevent and promote mental health disorders. This study aims to analyse the Islamic religious guidance approach for mental health disorders. This research uses qualitative methods with a literature study approach. The data collection strategy was sourced from seven published Scopus-indexed journal literature in 2018-2023 using the keywords "Islamic religion and mental health". The study found practical variations of Islamic religious guidance for mental health disorders, including religious lectures, Al-Quran therapy, prayer therapy, psycho-spiritual therapy, therapy for majelis taklim activities, zikir and shalawat therapy, tawba and istighfar therapy. The practical implications of research with Islamic religious guidance can help treat mental health disorders gradually and sustainably.